Implementation of Islamic Religious Education Learning Evaluation Through Daily Tests on Students' Learning Motivation UPTD SMP Negeri 4 Parepare - Evi Febrianti; Makki; Rosmiati Ramli; Andi Fitriani Djollong; Muhammad Nur Maallah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the implementation of learning evaluations for Islamic religious education through daily tests at UPTD SMP Negeri 4 Parepare and to find out students' learning motivation after implementing learning evaluations for Islamic religious education through daily tests at UPTD SMP Negeri 4 Parepare. The type of research used was field research conducted at UPTD SMP Negeri 4 Parepare, using a qualitative research approach, there were two data sources used, namely primary data sources including students and Islamic religious education teaching staff and secondary data sources including documentation results and various literature in the form of books, journals, articles related to research, the research instruments used are the researchers themselves, observation guidelines, interview guidelines and documentation guidelines, data collection techniques used are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and data collection and drawing conclusions. The research results showed that: 1) The implementation of learning evaluation for students' Islamic religious education through daily tests has gone well. 2) Students' learning motivation after implementing learning evaluations through daily tests tends to increas